Cystic fibrosis mutations delta F508 and G542X in Jewish patients. Issue 2 (February 1992) - Lerer, I; Sagi, M; Cutting, G R; Abeliovich, D
Abstract : We have screened our CF patients for mutations in exons 10 and 11 of the CFTR gene. Two mutations, delta F508 and G542X, have been found in 66 Jewish CF patients. The average frequency of the delta F508 mutation in the Jewish population is 33.8%. The G542X mutation accounts for 13% of the Ashkenazi CF mutations and has been found in three out of seven chromosomes of Jewish patients from Turkey (probably descended from Ashkenazi immigrants). The G542X mutation was not found in any of the other non-Ashkenazi patients. All the G542X bearing chromosomes have the same haplotype. Based on these observations it is concluded that the G542X mutation was introduced into the Jewish people after the split into Ashkenazi and non-Ashkenazi.